Influence of native field management on soil, water erosion and nutrient losses - Bagio, Bárbara; Bertol, Ildegardis; Wolschick, Neuro Hilton; Bernardi, Loriane; Oliveira, Marco Fruhauf de (Pesquisa agropecuária tropical, 2023)
ABSTRACT The native field area in southern Brazil has been reduced due to cultivation, and part of the remainder is traditionally burned and may increase water erosion and soil degradation. In this research, the soil chemical composition and water erosion, under natural rainfall, were evaluated in an Inceptisol, in the south of the Santa Catarina state plateau. The treatments consisted of native field, field mowed and burned once a year, and field cultivated under no-tillage conditions, in plots of 3.5 x 22.1 m and average slope of 10 %. The water erosion was evaluated between November 2016 and September 2018, when there were 61 erosive rainfalls, totaling 1,997 mm and 8,472 MJ mm ha-1 h-1. The soil losses were 82 kg ha-1 in the cultivated field, 55 kg ha-1 in the burned field and 24 kg ha-1 in the native field; and the water losses, in relation to the total rainfall, were 2.2 % in the native field and cultivated field and 1.2 % in the burned field. RESUMO A área de campo nativo no Sul do Brasil foi reduzida devido ao cultivo, e parte do remanescente é tradicionalmente queimada, podendo aumentar a erosão hídrica e a degradação do solo. Avaliou-se a composição química do solo e a erosão hídrica, sob chuva natural, em um Cambissolo Húmico, no sul do planalto Catarinense. Os tratamentos consistiram de campo nativo, campo roçado e queimado uma vez ao ano e campo cultivado em condição de semeadura direta, em parcelas de 3,5 x 22,1 m e declividade média de 10 %. A erosão hídrica foi avaliada entre novembro de 2016 e setembro de 2018, quando ocorreram 61 chuvas erosivas, totalizando 1.997 mm e 8.472 MJ mm ha-1 h -1. As perdas de solo foram de 82 kg ha-1 no campo cultivado, 55 kg ha-1 no campo queimado e 24 kg ha-1 no campo nativo; e as perdas de água, em relação ao total precipitado, foram de 2,2 % no campo nativo e campo cultivado e de 1,2 % no campo queimado.